Change in Radiating Leg Pain After Traffic Accidents in Patients With and Without Herniated Intervertebral Disc - Deok-Won Youn; Hui-Gyeong Jeong; Oh-Hoon Kwon; Ji-Hoon Choi (MEDrang Inc., 2017)
Background The aim of this study was to assess the change in radiating leg pain after traffic accidents in patients with and without herniated intervertebral disc (HIVD) and improvement of radiating leg pain after traffic accidents. Methods This was an retrospective study of 188 patients. Patients who had been admitted to the Hospital of Korean Medicine with the complaint of radiating leg pain after traffic accidents, and who had undergone lumbar spine magnetic resonance imaging to determine the presence or absence of HIVD were observed from April to June 2016. We analyzed sex, age, length of admission, direction (to a single leg or to both legs) and locations, (medial, anterior, lateral or posterior side of the lower limb) of radiating leg pain, presence or absence of HIVD, and number, grade and position of HIVD. The Numeric Rating Scale (NRS) and Oswestry Disability Index (ODI) were used to evaluate the impact of radiating leg pain on patients. Results Radiating leg pain NRS score decreased significantly in both the HIVD group (from 6.12 ± 2.39 to 4.31 ± 1.87, p < 0.001) and the no HIVD group (from 5.76 ± 1.64 to 3.85 ± 1.41, p < 0.001). ODI score also decreased significantly in both groups (HIVD, from 44.67 ± 17.38 to 26.83 ± 13.18; no HIVD , from 39.24 ± 15.58 to 19.69 ± 12.; both p < 0.001). Conclusions There was no significant change in radiating leg pain after traffic accidents in patients with and without HIVD and improvement of radiating leg pain after traffic accidents.